Simulation Analysis and Realization of Z-H Converter for Standalone PV Applications - N. Kalaiarasi; D. Anitha; S. Usha (EAI Endorsed Transactions on Energy Web, 2026)
INTRODUCTION: Power converter plays the major role of a power conditioning unit in solar photovoltaic (PV) system and acquiring the maximum power from the photovoltaic array. ZH converters are known for their ability to perform both buck and boost operations. This dual capability is crucial in solar energy systems where the output voltage from the PV array can vary due to factors like sunlight intensity and temperature. ZH converters are well suited for such applications due to their ability to operate in both buck and boost modes. OBJECTIVES: To design and validate the performance of a ZH converter that provides a wide range of flexible voltage regulation, thereby enhancing system adaptability and reliability by mitigating ripple and inrush currents.METHODS: In boost mode, the operating principles of both the ZH converter and ZSI (Z-source inverter) have the same characteristics. ZH converter has the same impedance network which is in the ZSI but with a different connection due to which the ZH converter has different features compared to that of ZSI. RESULTS: The simulation has been performed using MATLAB/Simulink software and prototype hardware is designed to verify the simulation results.CONCLUSION: The front-end diode and ST (shoot-through) switching state are removed in the ZH converter. Also, there is no requirement for an additional filter in the circuit because it generates a low ripple waveform. Therefore, the ZH converter can be put into effect various forms of power conversions like DC-DC, DC-AC, AC-DC, and AC-AC power conversion and can be used in photovoltaic applications.
Keywords: ZH converter; Z-source inverter; DC-DC converter; DC-AC converter; Photovoltaic array; Shoot-through; In-rush currents